Immersive horizons: navigating ethical terrain and practical boundaries in the use of virtual reality for cancer symptom management – a comprehensive narrative review - Siddiqui, Aisha R.; Kistipati, Hari C.; Asghar, Fatema A.; Bhimani, Sameer; Habib, Muhammad T.; Siddiqui, Farina F.; Anwar, Mariam; Gul, Muhammad H.; Hassan Ali, Hassan Ali; Khan, Muhammad M. (International Journal of Research in Medical Sciences, 2023)
Cancer is a significant healthcare problem. However, advancements in diagnostic procedures and therapeutic modalities have led to a decline in cancer mortality rates by 1% annually in most countries. Cancer patients often experience symptoms such as pain, cancer-related fatigue, anxiety, and lymphedema. To counter these side effects, there have been tremendous efforts. One such effort is the use of virtual reality (VR) technology, which is an interactive technology. VR has played a significant role in managing disorders such as phobias and anxiety disorders, and support for patients with cognitive and physical rehabilitation, acute and chronic pain management, and emotional support in different settings such as during hospitalizations. Our team conducted an extensive search for electronic literature on virtual reality in various databases, such as Medline, PubMed, Google Scholar, and Psych INFO, up to July 2023. We used keywords like "virtual reality," "cancer care," "depression," "cognition," "pain," "telemedicine," "rehabilitation care," "physical therapy," "radiotherapy," "telerehabilitation," "avatar," "video games," and "visual aid" as our search criteria. VR interventions for cancer patients include exposure therapy, psycho-education, and relaxation techniques, which have been shown to reduce symptoms significantly. VR distraction can also mitigate pain during medical procedures. Studies suggest that VR holds promise in rehabilitation and oncologic treatment, as it can improve function metrics, range of motion, and motivation for treatment. The review scrutinizes the use of digital information and virtual reality technology to alleviate cancer-related distress by providing remote care.